2001
DOI: 10.1152/ajpheart.2001.280.6.h2496
|View full text |Cite
|
Sign up to set email alerts
|

Extending fluorescent microsphere methods for regional organ blood flow to 13 simultaneous colors

Abstract: Seven fluorescent microsphere colors can be used in a single experiment to estimate regional blood flow without correcting for spillover of emitted fluorescence. To extend the method to 13 colors, we compared the accuracy of three methods for spillover correction. Fixed wavelength intensities were corrected by matrix inversion, and synchronous scan spectra were corrected by least squares fit of an overdetermined system of linear equations and by least squares fit of a sum of Gaussian and Lorentzian functions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…The availability of 13 different fluorescent labels has substantially expanded investigational opportunities for simultaneous measurements of both regional perfusion and regional ventilation with the small tissue samples (51). The correlation for simultaneously administered different FMS colors uniformly exceeds 0.99 for the standard ϳ2-cm 3 lung piece size, and these measurements correlate equally well with simultaneous measurements made with RMS (18).…”
Section: Advantages Of Microsphere Mapsmentioning
confidence: 89%
“…The availability of 13 different fluorescent labels has substantially expanded investigational opportunities for simultaneous measurements of both regional perfusion and regional ventilation with the small tissue samples (51). The correlation for simultaneously administered different FMS colors uniformly exceeds 0.99 for the standard ϳ2-cm 3 lung piece size, and these measurements correlate equally well with simultaneous measurements made with RMS (18).…”
Section: Advantages Of Microsphere Mapsmentioning
confidence: 89%
“…19 The simultaneous measurement of regional V and Q in small regions of the embolized lung was first accomplished more than a decade ago, by investigators who used a technique based on aerosolized and injected fluorescent microspheres (FMSs). [20][21][22] Their data made it possible to reconstruct all regions of the embolized lung post mortem, with each region designated for its own V/Q ratio 23 and mapped in three-dimensional (3D) coordinates. All emboli locations were also marked.…”
Section: Gas Exchange In Aptementioning
confidence: 99%
“…Eight fluorescent microsphere colors can be used in a single experiment to estimate RBF without correcting for spillover of emitted fluorescence. It has been reported that for 13 fluorescent colors, spillover error can be minimized so that all 13 colors provide accurate estimations of RBF [25]. In large animal studies, investigators often inject 6 to 18 million spheres during a single injection [8][9][10][11][12][13].…”
Section: Microsphere Protocolsmentioning
confidence: 99%
“…We demonstrated that eight serial injections totaling 18 million spheres administered over an extended protocol are feasible without concern for a statistically or substantively significant influence on RBF from excessive accumulation of microspheres in the capillaries after multiple, large injections. Therefore, using the 13-color technique [25], it may be possible to measure RBF in the same chronic preparation up to 13 times, provided that the cumulative injection of microspheres is less than 18 million spheres.…”
Section: Microsphere Protocolsmentioning
confidence: 99%